Answer:
[tex]g(x)=-x-5[/tex]
Step-by-step explanation:
if we reflect across the y-axis, the y-value is just being negated, or in other words from positive -> negative or negative -> positive depending on what the initial y-value was.
So if we have the function [tex]f(x)=x[/tex], then we just negate the x, since the x represents the y-value.
This gives us: [tex]g(x)=-x[/tex]
Now to translate 5 units down, the y-value is decreasing by 5 units, and since the -x represents the y-value, we just subtract 5 from it to get
[tex]g(x)=-x-5[/tex]